Possibility for large-scale production of 238Pu for radioisotope thermoelectrical generators in a supercritical light-water reactor - Anatoly N. Shmelev; Vladimir A. Apse; Vasily B. Glebov; Gennady G. Kulikov; Evgeny G. Kulikov; Anton E. Kruglikov (Nuclear Energy and Technology)
The paper analyzes the possibility for large-scale production of highly pure plutonium suitable for use in radioisotope thermoelectrical generators in a VVER-SKD light-water power reactor with supercritical coolant parameters. Neptunium dioxide (NpO2) was used as the starting material. Neptunium can be extracted from minor actinides, i.e. from the main components of radioactive transuranium waste. Large-scale production of useful high-purity plutonium via neutron irradiation of useless radioactive waste can be estimated as one of the possible ways to convert harmful waste to a harmless form. The assembly with the starting material was placed in the central part of the reactor core with the maximum neutron flux to increase the plutonium accumulation. Numerical studies were based on a multi-physical approach with coupled analyses of neutronic and thermal-hydraulic processes in the downward and upward reactor zones. The results obtained in numerical studies have demonstrated that large quantities of high-purity plutonium with a low content of 236Pu and a high content of 238Pu could be accumulated in the central NpO2 assembly if the following conditions are satisfied. Firstly, it is desirable that the lattice of NpO2-containing rods would be sufficiently wide with a high volume fraction of light-water coolant. Secondly, the central NpO2 assembly needs to be surrounded by protective assemblies to form a barrier against high-energy fission neutrons which are capable to intensify the threshold 237Np(n,2n)236Pu reaction. The protective function can be performed by the assemblies containing rods with natural lead or radiogenic lead. The paper estimates the production scales of high-purity plutonium in the central assembly with a wide lattice of NpO2-containing rods and surrounded by a layer of protective Pb-containing assemblies.